Tailoring the microstructure and mechanical properties of wire and arc additive manufactured Al–Mg alloy via interlayer friction stir processing - Li Liu; Wanghui Xu; Yunqiang Zhao; Zhicheng Lin; Zhe Liu; Yaming Dong; Chunlin Dong (Journal of Materials Research and Technology, 2023)
In this study, a hybrid additive manufacturing method was developed by combining the wire and arc additive manufacturing (WAAM) with a synchronously conducted interlayer friction stir processing (FSP). Straight walls were prepared using Er5356 wire, and interlayer FSP was conducted to modify the microstructure of the deposited layers. Special attention was paid to the effects of interlayer FSP on the microstructural evolution and mechanical properties of the manufactured Al–Mg alloy. Results show that the interlayer FSP can greatly decrease the size and density of pores in the additively manufactured Al–Mg alloy. The grains in the WAAM-FSP manufactured Al–Mg demonstrates layered distribution characteristics and grain refinement is achieved as compared to the WAAM sample. Both strengths and elongations in the vertical and horizontal directions of the manufactured Al–Mg alloy are enhanced by interlayer FSP. Grain refinement strengthening and porosity reduction mainly contribute to the improvement of the strength. The WAAM coupled with interlayer FSP is an efficient technique to refine grains and pores, and thus improve mechanical properties of additively manufactured Al–Mg alloys. These results can promote the development and application of additively manufactured Al–Mg alloys.